WEB PROFILE DAN MEDIA PROMOSI JASA LAUNDRY SEPATU IDE SHOES: Web Profile and Promotional Media;Idea Shoes;Information System. - Sany, Ezrifal; Mohdiaki, Amri (FORTECH (Journal of Information Technology), 2022)
Idea Shoes Laundry Shop is an entrepreneur who is engaged in the laundry/washing of shoes, all of whose activities are still using a manual system. The purpose of this research is to assist the store in designing a service information system at the Ide Shoes Store. This sales information system can help the store in terms of promoting its business to the public. The design of this information system uses a web-based method. With the design of a web profile and promotional media for this shoe laundry, it makes it easier for laundromats to introduce their business to many people.